The Power of Youth: Political Impacts of the "Fridays for Future" Movement - Marc Fabel; Matthias Flückiger; Markus Ludwig; Helmut Rainer; Maria Waldinger; Sebastian Wichert (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the impact of the “Fridays for Future” climate protest movement in Germany on citizen political behavior and explore possible mechanisms. Over the course of 2019, large crowds of young protesters, most below voting age, skipped school to demonstrate for rapid and far-reaching measures to mitigate climate change. Based on cell phone-based mobility data and hand-collected information on almost 4,000 climate protests, we first construct a novel county rally-specific measure of protest participation, allowing us to map out how engagement in the climate movement evolved spatially and temporally. Then, using a variety of empirical strategies to address the issue of nonrandom protest participation, we show that the local strength of the climate movement led to more Green Party votes in state-level and national-level elections during 2019 and thereafter. We provide evidence suggesting that three mechanisms were simultaneously at play: reverse intergenerational transmission of pro-environmental attitudes from children to parents, stronger climate-related social media presence by Green Party politicians, and increased coverage of environmental issues in local media. Together our results suggest that environmental protests by those too young to vote provides some of the impetus needed to push society towards overcoming the climate trap.
Keywords: D72; 330; climate protest movement; citizen political behavior